PROBLEMATIKA PROSES RESTORASI BUKU DENGAN KETERBATASAN SUMBER DAYA: STUDI KASUS DI PERPUSTAKAAN SMP NEGERI 6 KARAWANG BARAT - Zidny, Muhammad Haykal; Permana, Hinggil; Az Zahro, Fatimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School libraries play an important role as learning resource centers that support students’ literacy and academic activities. However, the high intensity of book usage often causes physical damage to collections, while restoration efforts are constrained by limited resources. This study aims to analyze the challenges in the book restoration process at the library of SMP Negeri 6 Karawang Barat. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving librarians and students. The results showed that restoration activities were still carried out despite limitations in budget, facilities, and human resources. Restoration was conducted in a simple manner using materials such as glue, tape, and staples to maintain the usability of collections. The study also found that low user awareness contributed to book damage. This study highlights the importance of strengthening preservation management, improving user awareness, and developing low-cost restoration strategies suitable for school libraries.